The influence of the vagus nerve and indole derivative SS-68 on excitation processes in the SA node - Anatoliy A. Nechepurenko; Pavel A. Galenko-Yaroshevsky; Vladimir M. Pokrovskiy; Anait V. Zelenskaya; Konstantin F. Suzdalev; Svetlana A. Lebedeva; Natalia M. Makhnova; Alexandr V. Maksemyuk; Ivan A. Minenko; Roman V. Nikitin; Valeriy G. Abushkevich (Belgorod National Research University, 2023)
Introduction: Atrial fibrillation (AF) is the most common form of cardiac arrhythmias. Studying the pathogenesis of this pathological process will make it possible to look for new methods of treating AF and to predict its occurrence in a more targeted way. The aim of the study was to identify the components of the takeover process of central rhythmogenesis by the SA node in the conditions of atrial fibrillation when stimulating the vagus nerve and using substance SS-68. Materials and Methods: The experiments were conducted on 30 frogs and 90 cats. In frogs, the activity of the regions of the medulla oblongata synchronous with the heart rhythm was determined in a high-frequency electromagnetic field. In cats, proximal and distal foci of luminescence in the vagus nerve (VN) and pools of pacemaker cells (PCs) in the sinoatrial node were visualized under topical and general anesthesia, using a KELSY scanner with a microscope video capture unit while stimulating VN and using SS-68. Results and Discussion: The stimulation of VN with volleys of electrical impulses and the introduction of SS-68 increase the foci of luminescence in the nerve and unite the PC pools. This way, under general anesthesia in comparison with topical anesthesia, the area of the proximal focus of VN luminescence decreased by 83.8%, and the distal focus - by 44.9%. Against the background of general anesthesia, the area of the proximal focus of luminescence when stimulating VN with volleys of electrical impulses was by 76.0% larger than before stimulation, and the distal focus - by 72.5%. After the administration of SS-68, there was an increase in the foci of luminescence: under general anesthesia, when compared with topical anesthesia, the area of the proximal foci of luminescence decreased by 86.8%, and the distal one - by 67.1%. Under general anesthesia, the area of the proximal focus of luminescence under conditions of stimulating VN with volleys of electrical impulses was by 82.2% larger than before stimulation and the distal one - by 78.2%. When signals from the brain arrive simultaneously through VN at the PC pools, they are absorbed by the PC pools; the focus of early depolarization becomes wide, which prevents the development of AF. The increased synchronizing influence of VN may be one of the methods for treating autonomic AF, and if its influence decreases, it can be a prognostic factor for the occurrence of recurrent AF. Conclusion: The tonic effect of VN on the heart rhythm through electrical stimulation of the former and the use of SS-68 is manifested in a decreased heart rate: the difference between the initial heart rhythm and the minimal synchronization range boundary. A decrease in the heart rate under the influence of VN prevents paroxysms of AF, but does not completely eliminate the influence of ectopic foci on it.